Progress and pitfalls of gene editing technology in CAR-T cell therapy: a state-of-the-art review - Moradi, Vahid; Khodabandehloo, Elnaz; Alidadi, Mehdi; Omidkhoda, Azadeh; Ahmadbeigi, Naser (Frontiers in Oncology, 2024)
CAR-T cell therapy has shown remarkable promise in treating B-cell malignancies, which has sparked optimism about its potential to treat other types of cancer as well. Nevertheless, the Expectations of CAR-T cell therapy in solid tumors and non-B cell hematologic malignancies have not been met. Furthermore, safety concerns regarding the use of viral vectors and the current personalized production process are other bottlenecks that limit its widespread use. In recent years the use of gene editing technology in CAR-T cell therapy has opened a new way to unleash the latent potentials of CAR-T cell therapy and lessen its associated challenges. Moreover, gene editing tools have paved the way to manufacturing CAR-T cells in a fully non-viral approach as well as providing a universal, off-the-shelf product. Despite all the advantages of gene editing strategies, the off-target activity of classical gene editing tools (ZFNs, TALENs, and CRISPR/Cas9) remains a major concern. Accordingly, several efforts have been made in recent years to reduce their off-target activity and genotoxicity, leading to the introduction of advanced gene editing tools with an improved safety profile. In this review, we begin by examining advanced gene editing tools, providing an overview of how these technologies are currently being applied in clinical trials of CAR-T cell therapies. Following this, we explore various gene editing strategies aimed at enhancing the safety and efficacy of CAR-T cell therapy.